Management of banded leaf and sheath blight of maize with chemicals - and ASHOK BHATTACHARYYA, K.C. PUZARI, U.N. SAIKIA (Indian Phytopathology, 2002)
One antibiotic and six fungitoxicants, viz., validacin, bavistin, captaf, contaf, rhizolex, indofil M-45 and kavach were tested against banded leaf and sheath blight of maize caused by Rhizoctonia solani Kuehn. Validacin (0.1%) followed by bavistin (0.1%) performed best in controlling the disease without any significant difference between them.